2020
DOI: 10.1038/s41562-020-0848-3
|View full text |Cite
|
Sign up to set email alerts
|

Shared striatal activity in decisions to satisfy curiosity and hunger at the risk of electric shocks

Abstract: Curiosity is often portrayed as a desirable feature of human faculty. However, curiosity may come at a cost that sometimes puts people in a harmful situation. Here, with a set of behavioural and neuroimaging experiments using stimuli that strongly trigger curiosity (e.g., magic tricks), we examined the psychological and neural mechanisms underlying the motivational effect of curiosity. We consistently demonstrated that across different samples, people were indeed willing to gamble, subjecting themselves to phy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 110 publications
10
82
1
Order By: Relevance
“…As a part of mental health, curiosity has a significant positive effect on our cognitive functions such as memory, learning, creativity, attention, subjective well-being, and prevention of psychological disorders. But previous research has shown that probabilistic electric shock, inducing one's stress, will inhabit the risk behavior of relieving the curiosity (Brown et al, 2020;Lau, Ozono, Kuratomi, Komiya, & Murayama, 2020). In our research, higher state anxiety during the COVID-19 time was correlated with the more depressive, fear and anger feeling, and less pleasure feeling.…”
Section: State Anxiety Interpersonal Distancing Autistic Tendency supporting
confidence: 39%
“…As a part of mental health, curiosity has a significant positive effect on our cognitive functions such as memory, learning, creativity, attention, subjective well-being, and prevention of psychological disorders. But previous research has shown that probabilistic electric shock, inducing one's stress, will inhabit the risk behavior of relieving the curiosity (Brown et al, 2020;Lau, Ozono, Kuratomi, Komiya, & Murayama, 2020). In our research, higher state anxiety during the COVID-19 time was correlated with the more depressive, fear and anger feeling, and less pleasure feeling.…”
Section: State Anxiety Interpersonal Distancing Autistic Tendency supporting
confidence: 39%
“…This rational framework of curiosity and the findings that support it strive to explain curiosity using the same computational and algorithmic principles derived from studying reward-based behavior 4,14,36 . Recently, curiosity has been implicated as a necessary core computation for natural and artificial intelligence 37,38 , with information and reward postulated to be the basic fungible currencies of cognition 6,16,36 .…”
Section: Discussionmentioning
confidence: 83%
“…We have already conducted one neuroimaging experiment using MagicCATs and validated the effectiveness of the stimuli. In Lau, Ozono, Kuratomi, Komiya, & Murayama (2020), we presented participants with a series of 36 magic trick video clips from MagicCATS to induce feeling of curiosity and asked them to decide whether they would be willing to risk receiving electric shocks to satisfy the curiosity to know the solution of the trick. Selfreported ratings of curiosity for each magic trick was significantly associated with the decision to accept the risk to receive electric shocks on a trial-by-trial basis, indicating that the magic trick videos successfully induced curiosity.…”
mentioning
confidence: 99%